PENINGKATAN KUALITAS WALKBILITY DI RUAS JALAN H.Z. MUSTOFA KOTA TASIKMALAYA - Nurmayadi, Dicky; Sholahudin, Farhan (Jurnal Arsitektur ARCADE, 2022)
Abstract: Walkability is an innovation concept in creating pedestrian path facilities that prioritize pedestrian comfort and minimize air pollution levels. The purpose of this study is to identify the application of the walkability concept in Tasikmalaya City, especially the H.Z. Musthofa to support the City of Tasikmalaya as a productive and sustainable city. The research uses a literature study methodology or literature review by reviewing books and journals related to walkability and other literature such as news and regulations. The results show that the application of the concept of walkability in Tasikmalaya City in realizing Tasikmalaya City as a productive and sustainable city is still very low when viewed from several global walkability index indicators. In realizing the City of Tasikmalaya as a pedestrian-friendly city, there are still some obstacles, such as the misuse of pedestrian paths as parking lots or as places or stalls for Street Vendors (PKL).Abstrak: Walkability merupakan sebuah konsep inovasi dalam menciptakan fasilitas jalur pedestrian yang mengutamakan kenyamanan pejalan kaki dan meminimalisir tingkat polusi udara.Tujuan penelitian ini adalah untuk mengidentifikasi penerapan konsep walkablility di Kota Tasikmalaya khususnya Ruas Jalan H.Z. Musthofa untuk mendukung Kota Tasikmalaya sebagai kota yang produktif dan berkelanjutan. Penelitian menggunakan metodologi studi kepustakaan atau literature review dengan menelaah buku dan jurnal terkait walkability serta litelature lainnya seperti berita dan regulasi. Hasil penelitian menunjukkan penerapan konsep walkability di Kota Tasikmalaya dalam mewujudkan Kota Tasikmalaya sebagai kota yg produktif dan berkelanjutan masih sangat rendah apabila dilihat dari beberapa indikator global walkability index. Dalam mewujudkan Kota Tasikmalaya sebagai Kota yang ramah bagi pejalan kaki masih ditemui beberapa hambatan seperti halnya penyalahgunaan jalur pedestrian sebagai lahan parkir maupun dijadikan tempat atau lapak Pedagang Kaki Lima (PKL).